Mesenchymal stem cells instruct a beneficial phenotype in reactive astrocytes. Issue 5 (31st December 2020) - Vigo, Tiziana; Voulgari‐Kokota, Androniki; Errede, Mariella; Girolamo, Francesco; Ortolan, Jasmin; Mariani, Maria C.; Ferrara, Giovanni; Virgintino, Daniela; Buffo, Annalisa; Kerlero de Rosbo, Nicole; Uccelli, Antonio
Abstract: Transplanted mesenchymal stromal/stem cells (MSC) ameliorate the clinical course of experimental autoimmune encephalomyelitis (EAE), a mouse model of multiple sclerosis (MS), reducing inflammation and demyelination. These effects are mediated by instructive cross‐talk between MSC and immune and neural cells. Astroglial reaction to injury is a prominent feature of both EAE and MS. Astrocytes constitute a relevant target to control disease onset and progression and, based on their potential to acquire stem cell properties in situ, to foster recovery in the post‐acute phase of pathology. We have assessed how MSC impact astrocytes in vitro and ex vivo in EAE. Expression of astroglial factors implicated in EAE pathogenesis was quantified by real‐time PCR in astrocytes co‐cultured with MSC or isolated from EAE cerebral cortex; astrocyte morphology and expression of activation markers were analyzed by confocal microscopy. The acquisition of neural stem cell properties by astrocytes was evaluated by neurosphere assay. Our study shows that MSC prevented astrogliosis, reduced mRNA expression of inflammatory cytokines that sustain immune cell infiltration in EAE, as well as protein expression of endothelin‐1, an astrocyte‐derived factor that inhibits remyelination and contributes to neurodegeneration and disease progression in MS. Moreover, our data reveal that MSC promoted the acquisition of progenitor traits by astrocytes. These data indicate that MSC attenuate detrimental features of reactive astroglia and, based on the reacquisition of stem cell properties, also suggest that astrocytes may be empowered in their protective and reparative actions by MSC. Main Points: Exogenous MSC prevent astrogliosis and reduce expression of astrocyte‐derived factors that sustain immune cell infiltration and inhibit remyelination in EAE. MSC promote acquisition of neural stem cell‐like phenotype in reactive astrocytes.